Could the Implementation of Augmented Reality Influence Consumers’ Purchase Intention in E-Commerce? - Iisnawati Iisnawati; Taufiq Marwa; Muchsin Saggaff Shihab; Yuliani Yuliani; Dessy Yunita; Islahuddin Daud (Jurnal Manajemen dan Kewirausahaan, 2023)
Augmented reality in e-commerce has become the latest trend in the world of online shopping. The purpose of this study is to empirically prove the influence of perceived of usefulness and the perceived ease of use towards behavioral intentions through attitudes. The urgency of this research is the new phenomenon of online shopping experience in Indonesia using augmented reality technology in e-commerce. This study used primary data by distributing questionnaires to 200 users of AR application in e-commerce with random sampling techniques. This study used Path analysis with SPSS. The results of the study prove that the perceived of usefulness and the perceived ease of use have a significant effect on online purchase intentions through attitudes. The perceived ease of use has more influence than the perceived of usefulness.